2020
DOI: 10.22323/2.19050209
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infections on international celebrities: self presentation and tweeting down pandemic awareness

Abstract: The novel coronavirus (COVID-19) which was first reported in China's Wuhan province in December 2019 became a global pandemic within a few months. The exponential rise in COVID-19 cases globally was accompanied by a spike in misinformation about the pandemic, particularly on social media. Employing Social Network Theory as a lens, this qualitative study explores how selected international celebrities appropriated their Twitter micro-blogging pages to announce their COVID-19 infection to the world. The study fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…With reference to moderating practices, some scholars have observed they could even strengthen conspiracy beliefs, and that banned content keeps circulating on alternative platforms (Bruns, Harrington, & Hurcombe, 2020), while others have even gone so far as to suggest, as a viable solution to counter disinformation, collaboration with platforms to imprison who spread fake news (Alvarez-Risco, 2020). Finally, although many papers focus on the role of social media in the infodemic, others have observed that they can also be used against it, for instance thanks to celebrities sharing quality information with their followers (Mututwa, 2020), or by official agencies to disseminate pandemic-related information (Liu & Tong, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…With reference to moderating practices, some scholars have observed they could even strengthen conspiracy beliefs, and that banned content keeps circulating on alternative platforms (Bruns, Harrington, & Hurcombe, 2020), while others have even gone so far as to suggest, as a viable solution to counter disinformation, collaboration with platforms to imprison who spread fake news (Alvarez-Risco, 2020). Finally, although many papers focus on the role of social media in the infodemic, others have observed that they can also be used against it, for instance thanks to celebrities sharing quality information with their followers (Mututwa, 2020), or by official agencies to disseminate pandemic-related information (Liu & Tong, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps, this is the way forward in making people realize threats and motivates them to change their behaviors. Mututwa et al [26] suggested that celebrities with a significant social media impact were able to successfully counter disinfodemic and promote awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Although responsible for a considerable flow of problematic information online, research has pointed out the positive role of social media in pandemic communication (Lovari & Righetti, 2021). For instance, it has been observed that celebrities can easily reach many followers with quality information (Mututwa, 2020), and while higher levels of social media use for both social support and information seeking are associated with higher levels of anxiety and depression (Drouin et al, 2020;Gao et al, 2020;Ni et al, 2020), social media can operate as allies of the institutions in reaching people with correct information, becoming protective agents supporting psychological well-being (Liu & Tong, 2020).…”
Section: Substantive Contentmentioning
confidence: 99%